2019
DOI: 10.3892/ijmm.2019.4305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes and miRNAs associated with neuropathic pain induced by spared nerve injury

Abstract: Neuropathic pain (NP) is a complex, chronic pain condition caused by injury or dysfunction affecting the somatosensory nervous system. This study aimed to identify crucial genes and miRNAs involved in NP. Microarray data (access number GSE91396) were downloaded from the Gene Expression Omnibus (GEO). Murine RNA-seq samples from three brain regions [nucleus accumbens, (NAc); medial prefrontal cortex, (mPFC) and periaqueductal gray, (PAG)] were compared between the spared nerve injury (SNI) model and a sham surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In silico analysis has shown some association of CXCR2 with atrial fibrillationpotential miRNAs that decrease CXCR2 expression are miR-5001-3p and miR-4283 [24]. Another in silico analysis of genes associated with neuropathic pain has shown that CXCR2 expression may be increased by reducing the expression of miR-7688-3p [25]. The study was associated with the earlier observation that CXCR2 is a receptor important in the development of neuropathic pain [26].…”
Section: Involvement Of Micrornas In the Regulation Of Cxcr2 Expressionsupporting
confidence: 55%
“…In silico analysis has shown some association of CXCR2 with atrial fibrillationpotential miRNAs that decrease CXCR2 expression are miR-5001-3p and miR-4283 [24]. Another in silico analysis of genes associated with neuropathic pain has shown that CXCR2 expression may be increased by reducing the expression of miR-7688-3p [25]. The study was associated with the earlier observation that CXCR2 is a receptor important in the development of neuropathic pain [26].…”
Section: Involvement Of Micrornas In the Regulation Of Cxcr2 Expressionsupporting
confidence: 55%
“…Similar to human studies, differentially expressed miRNAs are extensively explored in preclinical neuropathic pain models [31,[59][60][61][62][63][64]. In several of the routinely used models, specific miRNAs are up-or down-regulated all along the pain pathway and described in a number of recent publications and reviews [59,60,62,[64][65][66][67][68][69][70][71]. The following section takes a more mechanistic approach and provides an overview of miRNAs deregulated in tissues in relevant preclinical pain models for which a relevant target gene and insight into neuropathic pain mechanisms have been validated (see Table 3 ).…”
Section: Mirna Tissue Expression In Rodent Modelsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are noncoding genes that contain 19-25 nucleotides, which play a pivotal role in controlling biological processes by affecting messenger RNA (mRNA) stability and protein translation (Lopez-Gonzalez et al, 2017). There are a large number of reports of miRNA changes in the spinal cord of neuropathic pain models (Gong et al, 2015;Liu et al, 2018;Cao et al, 2019), whereas only a few studies have examined the mPFC (Li et al, 2019). We hypothesized that changes in miRNA and mRNA expression in the PL might influence behavioral changes in neuropathic pain and will become potential targets for pain control therapy.…”
Section: Introductionmentioning
confidence: 99%